Pemanfaatan Warisan Budaya Kete Kesu Dalam Pembelajaran Sejarah di SMA Negeri 1 Toraja Utara - Setiamin, Asnah; Jumadi, Jumadi; Ahmadin, Ahmadin; Najamuddin, Najamuddin (Riwayat: Educational Journal of History and Humanities, 2025)
This study focuses on three main topics: the suitability of Kete Kesu as a medium for teaching history at SMA Negeri 1 Toraja Utara, the forms of historical learning media available at Kete Kesu, and the implications of utilizing Kete Kesu as a medium for teaching history at the same school. Using a descriptive qualitative research method combined with a historical approach that includes four stages heuristics, criticism, interpretation, and historiography. Research results show that Kete Kesu is relevant to the curriculum and learning objectives. It is authentic and original, offers pedagogical potential to stimulate students' interest and motivation, and provides access to diverse learning media and practical aspects. Additionally, it is strategically located, safe, comfortable, and supported by adequate facilities. The forms of historical learning media found at Kete Kesu include Tongkonan (traditional houses), granaries, rante and menhirs, museums, and stone graves. The utilization of Kete Kesu has significant implications for students, teachers, and schools.Keywords: Kete Kesu, Learning Media, History Learning.